Passing on Cultural Identity Through the Value of Experience Creative Tourism in War Areas - Thinthan, Sukanda; Pangkesorn, Anucha (Journal of Multidisciplinary in Humanities and Social Sciences, 2023)
Cultural identity are of great importance reflect what is common which is a characteristic that represents the culture In this paper, we point out the importance of bringing in the cultural resources available in war zones. There are two elements caused by war: people and space. People refer to the war causing the migration of ethnically diverse groups to live in the area. Thus resulting in cultural integration under the coexistence in the form of dependence. Area means war history. It has created a tourist attraction today and is what attracts both Thai and foreign tourists to travel in the area. But due to the current problem of the concentration of tourists in major tourist cities this affects the sustainability of natural resources, culture and local identity. including the situation of the epidemic of COVID-19 this is the starting point for turning the crisis into an opportunity for quality tourism. Under the changing behavior of tourists, local people have adapted in a new way. That meet the changing needs of tourists prefer to travel in small groups and seek experiences in new attractions in this article will present information. Passing on cultural identity through the value of creative tourism experiences in war zones which consists of creative tourism Meaning and concept of creative tourism war area Cultural Identity and Tourism Experience leading to the presentation of new knowledge that is a thought process leading to the design of creative tourism strategies which can be applied in a variety of dimensions in the future.